MODERN METHODS AND ANCIENT TECHNOLOGIES OF RESTORATION AND RESTORATION OF SHOES - BABYCH, Antonina; LYPSKY, Tymofii; RADIKOVA, Anna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Restoration and restoration of shoes - a delicate, complex, often jewelry. It requires professionalism, experience, creative and creative approach and innate artistic taste of the master. In addition, restoration work often requires special equipment and materials for a number of rare and complex operations to completely restore the product and give it its original appearance or, conversely, "aging" of new shoes at the request of the customer. Shoe restoration allows a specialist to create using standard and non-standard materials, classic and advanced methods and techniques for replacing worn parts in the product, and also allows you to experiment with finishing compositions to give the product the appearance of "wear" and "abrasion", creating a "faded" "Color of the material and its" aged "structure, the effect of attrition or patina, metallic luster or vice versa giving the product a look of" rejuvenation "by updating the color, giving it strength, shine, overall finish and strengthening the structure of the material as a whole. Thanks to such methods of restoration it is possible to achieve not just the desired, but also almost unique result of work. The features of the stages of shoe restoration are investigated in the article. Technological stages of restoration of footwear and step-by-step technology of finishing of finished products have been developed. A full cycle of restoration works was carried out on samples of men’s shoes worn. Tested according to the requirements of the standards and experimentally proven high wear resistance of the surface of the materials of the restored shoes, namely: the ability of the material to repeated bending, stretching, wet and dry friction. Experimental wearing of restored shoe samples was carried out. The high operational characteristics of the studied products have been confirmed. The expediency of these works has been proved experimentally.